2022
DOI: 10.1177/10596011221076636
|View full text |Cite
|
Sign up to set email alerts
|

How and When Can Robots Be Team Members? Three Decades of Research on Human–Robot Teams

Abstract: Artificial intelligence and robotic technologies have grown in sophistication and reach. Accordingly, research into mixed human–robot teams that comprise both robots and humans has expanded as well, attracting the attention of researchers from different disciplines, such as organizational behavior, human–robot interaction, cognitive science, and robotics. With this systematic literature review, the authors seek to establish deeper insights into existing research and sharpen the definitions of relevant terms. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 174 publications
0
2
0
Order By: Relevance
“…While many studies have shown that the use of agents improves outcomes (Fan & Yen, 2010;Wright et al, 2016), this research has examined how team processes are affected by software agents. As existing research on robots as team members (Wolf & Stock-Homburg, 2022;You & Robert, 2018b) has focused on trust or acceptance, it might be worthwhile to extended this also to analyze social processes within human-autonomy teams. This study suggests that future research should be aware of more complex processes (e.g., IMOI-model, You & Robert, 2018a;Shoemaker et al, 2016) that are influenced by software agents.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…While many studies have shown that the use of agents improves outcomes (Fan & Yen, 2010;Wright et al, 2016), this research has examined how team processes are affected by software agents. As existing research on robots as team members (Wolf & Stock-Homburg, 2022;You & Robert, 2018b) has focused on trust or acceptance, it might be worthwhile to extended this also to analyze social processes within human-autonomy teams. This study suggests that future research should be aware of more complex processes (e.g., IMOI-model, You & Robert, 2018a;Shoemaker et al, 2016) that are influenced by software agents.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Robots with human teams are used in various disciplines like search and rescue, space exploration, and minimally invasive surgeries. Human-Robot Teams (HRTs) are multiple-member collaborative teams exhibiting task interdependencies (Wolf and Stock-Homburg, 2022) Robots which interact naturally with humans, work as partners and interact socially with humans to get tasks done are called Social Robots (Cagiltay et al, 2020). The exploration of the social dynamics and how Social Robots integrate into HRTs as part of our daily lives is still nascent.…”
Section: Introductionmentioning
confidence: 99%